The health of populations general theories and particular realities - Kunitz, Stephen J. (New York ; Oxford : Oxford University Press, 2007)
In the maelstrom of current public health debate over the social determinants of health, this book offers a discussion on the roots of prevalent strains of thought on the matter. The author brings an independent perspective to bear on the debate.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health -- Economic aspects; Public health -- Social aspects; Public health -- History; Industrialization -- Health aspects; Population -- Health aspects